Magnetic resonance imaging in the diagnosis of non-tumorous multifocal brain lesions mimicking multiple sclerosis - Krotenkova, I. A.; Bryukhov, V. V.; Konovalov, R. N.; Zakharova, M. N.; Krotenkova, M. V. (Alʹmanakh klinicheskoĭ medit͡s︡iny, 2021)
The diagnosis of multiple sclerosis (MS) is quite challenging due to its variable clinical manifestations and lack of a  definitive test. Magnetic resonance imaging (MRI) is one of the tools to confirm the diagnosis and also helps in differential diagnosis with other disorders and in exclusion of MS-mimicking diseases. In this article, based on the analysis of clinical cases, we discuss the differential diagnosis of MS with the following non-tumorous multifocal brain lesions: vascular abnormalities caused by hypoxia and ischemia, cerebral autosomal dominant angiopathy with subcortical infarctions and leukoencephalopathy, Susac syndrome, primary angiitis of the central nervous system, and neurosarcoidosis. We present both MRI criteria for MS and disorders that have similar MRI signs, and additional clinical and laboratory data that is essential for correct diagnosis.